Diseño de un sistema de gestión de la calidad para el mejoramiento continuo de la empresa Akhtar Consultoresso S.A. - Caza Collaguazo, Diego Joel (2024)
The purpose of this study is to design a quality management system for the continuous improvement of the company AKHTAR CONSULTORESSO S.A, to expand the quality of products and services. In the research, the current state of the company was analyzed, developing a process where the products and services are identified, by measuring methods and recognizong the causes of the deficiency in the SWOT method, and Ishikawa diagram. Proposing perfection and devepoling A PVHA cycle philosophy. The study is planned as a non-experimental investigation and a field modality is adopted, applying on-site visits carried out in the organization and data required to know the current state of the company, using interviews and checklists for the design a quality management system. The results hepls to recognize the operative problems in the process, as well as the low quality of the company's products due to the care of the 5S tool of the Lean Manufacturing methodology for the Warehouse-Store. Quality services are owed to the attention of a management system to eliminate mistakes and have continuous advancement. The study of the company AKHTAR CONSULTORESSO S.A. Concluded. highlights the need to improve the quality of its products and services by proposing a Lean Manufacturing methodology and an eminence management system. The strategy of a 5S Guide and a Quality Manual provides an increase in customer satisfaction.